Exploring Online Morphology Instruction For EFL Learners: Opportunities And Challenges - Mezia Kemala Sari; Suci Rahmah Safinatunnajah (FKIP UMSB, 2025)
The rapid shift to online learning following the COVID-19 pandemic has transformed instructional practices in higher education, including the teaching of linguistics courses such as morphology. Morphology, as a core component of linguistic competence, plays a crucial role in vocabulary development, word recognition, and language comprehension for English as a Foreign Language (EFL) learners. This article aims to explore the opportunities and challenges of teaching English morphology through online learning environments. Employing a descriptive qualitative approach, this study is based on a critical review of relevant literature, reflective teaching experiences, and observation of online instructional practices in English education programs. The discussion highlights how digital platforms, multimedia resources, and visual learning tools provide significant opportunities to enhance students’ morphological awareness and engagement. Online instruction allows for the use of videos, animations, and interactive materials that support students’ understanding of word formation processes such as affixation, compounding, borrowing, and coinage. However, the study also identifies several challenges, including limited internet access, technical difficulties, reduced interaction, and students’ varying levels of digital literacy. Despite these constraints, effective instructional design and creative use of digital media can mitigate many of these obstacles. The article concludes that teaching morphology online is not merely an alternative mode of instruction but a viable and innovative approach that can enrich language learning when supported by appropriate pedagogical strategies.